Tourist Loyalty Model in Bukit Lawang: Hedonism, Susceptibility, and Brand Love - Nasib; Salqaura, Siti Alhamra (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
This study aims to examine a tourist behavior model by investigating the effects of hedonism, perceived susceptibility, and brand love on tourist loyalty at the Bukit Lawang tourism destination. A quantitative approach was employed, utilizing a survey method with a total of 387 respondent. The collected data were analyzed using path analysis. The findings reveal that hedonism has a significant direct effect on both brand love and tourist loyalty. Perceived susceptibility significantly influences brand love but has no direct effect on loyalty. Brand love is shown to have a direct positive impact on loyalty. Furthermore, hedonism indirectly influences tourist loyalty through the mediating role of brand love. In contrast, perceived susceptibility does not exhibit a significant indirect effect on loyalty via brand love. These findings highlight the mediating role of emotional attachment (brand love) in translating hedonic experiences into tourist loyalty, particularly in nature-based tourism settings like Bukit Lawang.